PENGAWASAN KOMISI PENYIARAN INDONESIA DAERAH PROVINSI RIAU TERHADAP LEMBAGA PENYIARAN BERLANGGANAN MELALUI KABEL (STUDI KASUS TV KABEL ILEGAL DI KOTA PEKANBARU) - Josua Butar-Butar; Arief Rifa'i (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2019)
This study aims to determine and analyze the implementation of the Supervision Of The Indonesian Broadcasting Commission Regional Of Riau Towards Subscription Broadcasting Institutions Via Cable (Case Study Of Illegal Cable Television In Pekanbaru). The supervisory assessment indicators used include direct supervision and indirect supervision. This type of research located in the office of the The Indonesian Broadcasting Commission Regional Of Riau is a descriptive survey, which prioritizes questionnaires as a tool for collecting data and data collected with this tool and then becomes the main raw material for analyzing empirical conditions and objectivity of the existence of research objectives at meticulous locations. There are 3 population groups and the sample in this study is the commissioner of the Riau Regional Indonesian Broadcasting Commission, totaling 7 people’s. The leaders of Cable Television Subscription Broadcasting Institutions, totaling 15 people’s, and the cable Television customer community in Pekanbaru City, totaling 30 people’s. The sample size determined from these three groups is 52 people’s. The two sampling techniques used in assigning individual samples are census techniques for the commissioner population of The Indonesian Broadcasting Commission Regional Of Riau and incidental techniques for the community population of Cable Television customers. The types and data collection techniques used consist of, primary data collected using questionnaire list techniques and interviews and secondary data collected using observation techniques. While the data analysis technique used is by using a frequency table tool. Based on this analysis technique the researcher assessed and concluded that the Supervision Of The Indonesian Broadcasting Commission Regional Of Riau Towards Subscription Broadcasting Institutions Via Cable (Case Study Of Illegal Cable Television In Pekanbaru) was at a fairly intensive assessment interval. Recommendations that need to be considered are completing a comprehensive database related to the Cable Television industry in Pekanbaru City, making technical instructions for implementing internal sensor devices for Cable Television, regulating broadcasting infrastructure in Pekanbaru City, and socializing the application of Broadcasting Behavior Guidelines and Standard Broadcast Programs for Subscription Broadcasting Institutions Cable Television.